2014
DOI: 10.1590/1519-6984.02512
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and survival curves of Rhinella icterica (Anura, Bufonidae) under laboratory conditions

Abstract: Life tables and survival curves of tadpoles from Rhinella icterica species were studied in the laboratory, under abiotic conditions controlled by a purification filter, a timer and a chiller. The survival curve for larval stage confirms a great mortality trend in the initial stages, which decreases when reaching the mature morphological condition (r = -0.94). Stages 37, 38, 39, 40 and 41 showed gradual values for their age structures, while stages 42, 43 and 44 presented high variations. Based on the results u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The results found in the development of tadpoles in a cleaning filtration system were already encountered for Rhinella icterica (LIMA et al, 2014) with a maximum mortality rate of 7% in 2% of the ones found in this study. Given that the highest rate was 5%, it is similar to the result found in this study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations

Method of tadpoles in a closed system with filtration

Sérgio Cruz Souza Lima,
Leite Carnib de Sousa,
Pederassi
et al. 2023
CadUniFOA
“…The results found in the development of tadpoles in a cleaning filtration system were already encountered for Rhinella icterica (LIMA et al, 2014) with a maximum mortality rate of 7% in 2% of the ones found in this study. Given that the highest rate was 5%, it is similar to the result found in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Testing the qualities of the aquarium drum while following the development of the species Leptodactylus macrosternum Miranda-Ribeiro, 1926 through the structured model of the investigated population (GOTELLI, 2007;LIMA et al, 2014).…”
Section: Biologicalmentioning
confidence: 99%
See 1 more Smart Citation

Method of tadpoles in a closed system with filtration

Sérgio Cruz Souza Lima,
Leite Carnib de Sousa,
Pederassi
et al. 2023
CadUniFOA
“…Lima and Pederassi (2012) and Lima et al (2014) showed studies in which the stage progress decreases the probability of mortality, but reduces the population size of the species.…”
Section: Introductionmentioning
confidence: 99%
“…The results pointed out by the Kaplan-Meier estimator were similar to those calculated by the modified model ofSmith-Gill & Berven (1979) and ensured that the failures (dying, interrupting, recovering development) were present in the model, not neglecting any of the results, which makes this model a better condition than the Life Table, which disregards all failures.If we chose the Life Table(LIMA et al, 2014) to follow the development of tadpoles, we would have grouped results and would not represent the exact survival time, with failures, for each monitored individual. This change in statistical analysis is recommended for non-parametric samples in which the sample is subject to a set of faults(ZAR, 2010;GOTELLI & ELLISON, 2016), so the predicted and Kaplan-Meier results fit and represent a strong model for evaluation of tadpole development.…”
mentioning
confidence: 99%